Are restricted and repetitive behaviours in two‐ and six‐year‐olds associated with emotional and behavioural difficulties? - Sarah J. Carrington; Mirko Uljarević; Elizabeth Meins; Charles Fernyhough; Helen McConachie; Ann Le Couteur; Susan R. Leekam (Wiley, 2024)
Abstract Background Restricted and repetitive patterns of behaviour (RRBs) serve an adaptive role in development. Elevated levels of RRBs beyond the early years, however, are associated with poorer outcome in language, cognition, and wellbeing, and are seen across a range of neurodevelopmental conditions. This study aimed to characterize the association of distinct RRB subtypes at two and six years of age, with internalising and externalising difficulties in a community sample of children. Methods 485 parents reported on their child's insistence on sameness (IS) and repetitive sensory and motor (RSM) RRBs at two and six years of age using the Repetitive Behaviour Questionnaire (RBQ‐2). Emotional and behavioural difficulties were measured using the Strengths and Difficulties Questionnaire (SDQ) at age six. Results Consistent with previous research, RRBs later in development better predicted emotional and behavioural difficulties at age six than RRBs earlier in development. Moreover, IS RRBs were selectively associated with internalising behaviours and RSM RRBs with externalising behaviours. Importantly, these selective associations depended on when RRBs were measured. Only IS RRBs at age six were significantly associated with internalising behaviour. By contrast, while more RSM RRBs at age six were associated with higher rates of externalising behaviours, higher rates of RSM RRBs at age two were associated with fewer externalising behaviours, adding further support to the previously reported adaptive role of RRBs in early behaviour regulation. Conclusion Although there is a need for further research to provide a detailed profile of the adaptive periods for IS and RSM RRBs, the present findings support the potential utility of elevated RRBs as a signal for emotional and behavioural difficulties at age six.